Usuń nawiasy i wykonaj redukcję wyrazów podobnych:
a) (2x(2)-potęga)+4x-3) + (-x(2)-potęga -2x+4)
b) (3/5m(2)-potęga + 2/3n(2)-potęga +6) + ( -1/3m(2)-potęga - 2/3n(2)potęga-2 i3/5)
c) ( 0.5xy(2)-potęga - 1.2y(2)-potęga +5) + ( -0.8y(2)-potęga - 2,5xy(2)potęga- 2- 1/8)

1

Odpowiedzi

2010-01-26T18:26:45+01:00
A) (2x²+4x-3) + (-x² -2x+4)=2x²+4x-3-x²-2x+4=
=2x²-x²+4x-2x-3+4==x²+2x+1
b) (3/5m² + 2/3n² +6) + ( -1/3m²- 2/3n²-2 ³/₅)=
=³/₅m²+²/₃n²+6-¹/₃m²-²/₃n²-2 ³/₅=
=³/₅m²-¹/₃m²+²/₃n²-²/₃n²+6-2 ³/₅=
=⁹/₁₅m²-⁵/₁₅m²+5 ⁵/₅-2 ³/₅=⁴/₁₅m²+3 ²/₅
c)( 0.5xy² - 1.2y² +5) + ( -0.8y² - 2,5xy²- 2- 1/8)=
=0,5xy²-1,2y²+5-0,8y²-2,5xy²-2-¹/₈=
=0,5xy²-2,5xy²-1,2y²-0,8y²+5-2-¹/₈=
=-2xy²-2y²+3-¹/₈=-2xy²-2y²+2 ⁸/₈-¹/₈=-2xy²-2y²+2 ⁷/₈
6 4 6